Association of Serum 25 (OH) Vitamin D With Chronic Kidney Disease Progression in Type 2 Diabetes - Duan, Suyan; Lu, Fang; Wu, Buyun; Zhang, Chengning; Nie, Guangyan; Sun, Lianqin; Huang, Zhimin; Guo, Honglei; Zhang, Bo; Xing, Changying; Yuan, Yanggang (Frontiers in Endocrinology, 2022)
Objectives Growing evidence demonstrated that vitamin D levels had been linked to type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) in light of various extraskeletal effects. Therefore, the present study aimed to evaluate the association of 25-hydroxyvitamin D [25(OH)D] level with the clinicopathological features and CKD progression in T2DM. Methods A total of 182 T2DM patients with CKD stages 1 through 4 (G1-G4) were retrospectively included. Identification of serum 25(OH)D level associated with CKD progression was executed by Kaplan-Meier survival analysis and Cox proportional hazards models. We further performed sensitivity analyses with a time-weighted average (TWA) of serum 25(OH)D level in 75 participants to reinforce the ﬁndings. Results Median serum 25(OH)D level was 25.8 (IQR 14.4, 38.8) nmol/L in the study participants. Median follow-up time was 41.8 months, during which 70 (38%) patients confronted CKD progression. Cumulative kidney outcomes were significantly higher in the lowest tertile of serum 25(OH)D level in Kaplan-Meier analyses (P<0.001). Consistently, the analyses of Cox proportional hazards regression models indicated a significantly greater risk for CKD progression in the lowest tertile of serum 25(OH)D level compared with the highest tertile of serum 25(OH)D level (P=0.03). These relationships remained robust with further sensitivity analysis of data with TWA of serum 25(OH)D level, showing an independent association between lower TWA of serum 25(OH)D level and an unfavorable renal outcome in T2DM patients with CKD. Conclusions Our findings demonstrated that T2DM patients with a decreased 25(OH)D level had deteriorated renal function. Both lower levels of baseline and TWA of serum 25(OH)D were associated with an increased risk of CKD progression in T2DM patients, which suggested that long-term maintenance of optimal vitamin D levels from early in life might be associated with reduced future risk of CKD development in T2DM.